Model reduction in vehicle dynamic systems. (3rd April 2017) - Singh, R.; Singh, M.; Bera, T. K.
Abstract: A mathematical model describing the dynamic characteristics of the vehicle needs to be solved for predicting the future position and orientation of vehicle relative to the changing environment. By reducing the time consumed to solve the complex model, the cycle time for the overall process can be decreased. The work done in this paper, attempts to reduce the computational time by mathematically finding the redundant elements, which do not add to the major dynamics of the system but increase the calculation time by increasing the system complexity. Here, in this paper, eigenvalue separation and eigenvalue sensitivity methods have been applied to the different bond graph models of bicycle vehicle with suspension system, antilock braking system, steering system and four wheel vehicle models. The reduced system behaviour is similar to the response from the actual bond graph model. This method is applicable to linear systems as well as for the non-linear systems after certain modifications.